Enhancing User Experience through UI Redesign Using the UEQ+ Method - Setiawan, Wahyu Fajar; Amirullah, Afif; Rochimah, Siti (JOIV : International Journal on Informatics Visualization, 2025)
This research redesigned the User Interface (UI) of the XYZ e-wallet application, applying the User Experience Questionnaire Plus (UEQ+) testing method within the Design Thinking framework. This research contributes to the field by addressing the absence of comprehensive UI/UX evaluation in financial technology applications through an iterative design methodology. Initial UEQ+ assessment utilizing nine user experience questionnaire scales revealed significant usability issues, with intuitive use scoring 2.32 and clarity scoring 2.60, indicating substantial potential for improvement. The five stages of Design Thinking (Empathize, Define, Ideate, Prototype, Test) were systematically applied to solve the identified problems. Interactive prototyping in Figma facilitated real user testing of critical features, including the homepage, QRIS Payment, and History & Transfer notify. Post-redesign, there were significant increases in intuitive use (from 2.34 to 3.91; 67.1%), clarity (from 2.90 to 4.33; 49.3%), efficiency (from 3.25 to 4.44; 36.6%), trust metrics (from 3.41 to 4.51; 32.3%), and content quality (from 3.07 to 4.34; 41.4%). The statistical validation yielded a Cronbach’s Alpha of 0.965, indicating excellent reliability of the measurement. The high relationship among the factors (0.313-0.960) reflects a broad improvement. This study introduces the first empirically validated model that combines UEQ+ evaluation with Design Thinking for e-wallet applications, offering evidence-based UI/UX design guidelines for fintech, particularly valuable for Indonesian and similar developing markets where trust critically affects adoption.